Probabilistic Evaluation of Structural Pounding Between Adjacent Buildings Subjected to Repeated Seismic Excitations - Mohamed Nazri, Fadzli; Miari, Mahmoud Ali; Kassem, Moustafa Moffed; Tan, Chee Ghuan; Farsangi, Ehsan Noroozinejad (Springer, 2019)
This research investigates the effects of structural pounding (collision of structures) caused by insufficient gaps between adjacent buildings when subjected to repeated earthquakes. The structural performance of adjacent buildings experiencing structural pounding under the effect of moderate repeated ground motions is analyzed using incremental dynamic analysis. Fragility curves for different performance levels are developed to represent the capacity of the adjacent buildings. Two four-story and two ten-story frames, regular and irregular, are combined to represent nine different cases of structural pounding and subsequently analyzed under three artificial seismic sequences. Three gap cases that measure 1 mm (contact structures), 10 cm, and 1 m are assigned to consider possible pounding combinations. Analysis results show that structural damage is directly proportional to ground motion intensity and structural irregularity and inversely proportional to gaps between structures. A minimum spacing of 1 m is proposed for buildings in areas that experience repeated earthquakes to avoid structural pounding. In regular frames, main damage is concentrated in the bottom story beams. Meanwhile, damage in irregular frames is concentrated in top and bottom story beams. Hence, additional stiffness that corresponds to the height of short buildings should be assigned to beams (immediate above and bottom). Meanwhile, the damage is concentrated in ground floor columns. Therefore, to avoid soft story failure mechanism, additional stiffness should be added to columns at bottom stories, especially on the ground floor. Based on the obtained results, modern seismic design codes need to be updated to address these findings on structural pounding to reduce damage in adjacent buildings during moderate to major seismic events. © 2018, King Fahd University of Petroleum & Minerals.